Analisis Semiotika Roland Barthes Pada Iklan Aqua Versi “Aqua 100% Murni, 100% Indonesia - Febriana, Elisa; Nursanti, Siti; Hariyanto, Fajar (Peneliti.net, 2025)
Advertisement is an important element in the world of marketing that has a strategic role in influencing consumer behavior and creating awareness of a product. Advertisements not only play a role as a means of promotion, but also as a medium to influence consumer behavior and create an image of a product. Early in 2024, one of the largest mineral water products in Indonesia released its latest advertisement with the tagline